Verification of the three-dimensional modular nodal method for spherical harmonic equations - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 1996)
The three-dimensional nodal neutron transport code based upon a modular least squares approximation is used for solving various problems for verifying the method. While the code provides successful comparable results for some benchmark problems, it fails for another problem. In addition, the concept of modularity is tested for some problems and shown to be a viable approach to be implemented in transport computations.
Keywords: TRANSPORT